Molecular and morphological characterization of the metacercariae of two species of diplostomid trematodes (Platyhelminthes, Digenea) in freshwater fishes of the Batalha River, Brazil - Pelegrini, Larissa Sbeghen [UNESP]; Gião, Thayana; Vieira, Diego Henrique Mirandola Dias [UNESP]; Müller, Maria Isabel [UNESP]; da Silva, Reinaldo José [UNESP]; de León, Gerardo Pérez-Ponce; de Azevedo, Rodney Kozlowiski; Abdallah, Vanessa Doro (Springer Nature, 2019)
The Diplostomidae include a large group of flatworms with complex life cycles and are frequently found parasitizing the eyes and central nervous system of freshwater fishes. The morphological identification of the metacercariae at species level is not always possible. Thus, molecular tools have become essential to assist in the parasite species determination. This study was aimed at describing two diplostomid metacercariae found in freshwater fish in São Paulo, Brazil, based on morphological characters and in the genetic characterization of COI sequences. Our results showed that the two recognized taxa (Tylodelphys sp. and Diplostomidae gen. sp.) appear to be different from the species already described in South America. Tylodelphys sp. differs morphologically from Tylodelphys xenopi, T. mashonense, T. jenynsiae, and T. scheuringi. The metacercariae of T. clavata and T. conifera are smaller than Tylodelphys sp., while T. podicipina is larger than the metacercariae described here. The phylogenetic analysis of COI sequences yielded Tylodelphys sp. as the sister species of Tylodelphys sp. 4, a species reported from the brain of the eleotrid Gobiomorus maculatus in Oaxaca, Mexico. The metacercariae identified as Diplostomidae gen. sp. are morphologically different from the known diplostomid metacercariae and did not match with other diplostomid sequences available. Diplostomidae gen. sp. is recovered as the sister species of Diplostomum ardeae. Although the morphological evidence and the COI sequences differentiate the metacercariae found, the absence of adult specimens of both species precludes the specific designation. This is one of the first papers that use an integrative taxonomy approach to describe the species diversity of diplostomid trematodes in Brazil.
Keywords: Bayesian analysis; Cytochrome c oxidase; Fish parasites; Flatworms; Morphological analysis; Trematoda